2021
DOI: 10.1002/app.51657
|View full text |Cite
|
Sign up to set email alerts
|

An analytical approach to elucidate the architecture of polyethyleneimines

Abstract: Polyethyleneimine (PEI) is a common polymer used in many industrial applications and in research, especially in surface chemistry. It is available in a wide range of molecular weights and different degrees of branching. It is classified as linear or branched and sometimes the term hyperbranched is also used. This description, however, is quite rough, which limits the possibility to correlate the structure of the PEI to its properties. The aim of this study is to provide analytical tools to characterize the pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 22 publications
4
22
0
Order By: Relevance
“…The corresponding peaks of the stretching and bending vibration of C-H bond appeared at 2800-3000 cm −1 and 1300-1500 cm −1 , respectively [40][41][42][43], as our findings also illustrated these absorption ranges as small peaks (Figures 4(b) and 4(c)). Moreover, previous findings reported that the absorption peak range of 1500-1650 cm −1 and 3000-3400 cm −1 were ascribed to N-H 7 Journal of Nanomaterials bending and stretching vibration region related to the amine groups of PEI molecules [44][45][46], which are illustrated in Figure 4(c) as a broad peak in the region of 3000 to 3500 cm −1 that seems to be overlapped with the peaks of O-H stretching vibrations.…”
Section: Resultsmentioning
confidence: 81%
“…The corresponding peaks of the stretching and bending vibration of C-H bond appeared at 2800-3000 cm −1 and 1300-1500 cm −1 , respectively [40][41][42][43], as our findings also illustrated these absorption ranges as small peaks (Figures 4(b) and 4(c)). Moreover, previous findings reported that the absorption peak range of 1500-1650 cm −1 and 3000-3400 cm −1 were ascribed to N-H 7 Journal of Nanomaterials bending and stretching vibration region related to the amine groups of PEI molecules [44][45][46], which are illustrated in Figure 4(c) as a broad peak in the region of 3000 to 3500 cm −1 that seems to be overlapped with the peaks of O-H stretching vibrations.…”
Section: Resultsmentioning
confidence: 81%
“…As can be seen, the vibrational modes in the frequency region from ∼700 to 1700 cm –1 consisted of N–H bending and CH 2 rocking motions, that is, N–H bending at 777 cm –1 , C–N stretching at 1115 cm –1 , and N–H bending mixed with CH 2 scissors at 1456 cm –1 . The appearance of an absorption band at ∼1600 cm –1 with a shoulder at 1666 cm –1 was attributed to the absorption of N–H bending from the primary amines of branched PEI . The strong peak at 2818 cm –1 with a shoulder at 2938 cm –1 corresponds to the C–H stretching and bending vibrations of CH 2 in PEI.…”
Section: Resultsmentioning
confidence: 94%
“…The appearance of an absorption band at ∼1600 cm −1 with a shoulder at 1666 cm −1 was attributed to the absorption of N−H bending from the primary amines of branched PEI. 39 The strong peak at 2818 cm −1 with a shoulder at 2938 cm −1 corresponds to the C−H stretching and bending vibrations of CH 2 in PEI. In addition, another strong band related to N−H stretching was observed to be centered at 3279 cm −1 .…”
Section: Resultsmentioning
confidence: 99%
“…Branched variants of PEI are usually synthesized by the ring opening polymerization of aziridine (Gleede et al, 2019), where as linear PEI can be synthesized by modification of polymers like poly(2‐oxazolines) (Brissault et al, 2003). A large proportion of PEI's mass consists of amine groups, which confer a positive charge to the compound (Grenda et al, 2021). PEI molecules having high cationic charge form complexes with polyanionic DNA/RNA to form a PEI–nuclei acid complex (nanoplex).…”
Section: Introductionmentioning
confidence: 99%
“…A large proportion of PEI's mass consists of amine groups, which confer a positive charge to the compound (Grenda et al, 2021). PEI molecules having high cationic charge form complexes with polyanionic DNA/RNA to form a PEI-nuclei acid complex (nanoplex).…”
mentioning
confidence: 99%